Touch-flavor transference: Assessing the effect of packaging weight on gustatory evaluations, desire for food and beverages, and willingness to pay - Kampfer, K; Leischnig, A; Ivens, BS; Spence, C (Public Library of Science, 2017)
Product packaging serves a number of distinct functions and influences the way in which consumers respond to various product offerings. The research reported here examines whether the haptic characteristics of a non-diagnostic product packaging cue, namely its weight, affects the response of consumers. This article reviews existing research on haptic transference and proposes a conceptual framework to explore how the weight of product packaging affects the flavor of the food or beverages, and, in turn, consumers' desire for consumption and willingness to pay. Two studies demonstrate that an increase in packaging weight affects both desire and willingness to pay for the product. These effects are serially mediated by perceived flavor intensity and overall flavor evaluation. Based on these insights, implications for the design of food and beverages packaging are discussed.